Analysis of the Implementation of Digitization at the National Archives of the Republic of Indonesia - Astuty Rihanna; Prof. Dr. Henry Eryanto, M.M.; Dr. Terrylina Arvinta Monoarfa, SE., MM. (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The aim of this research is to examine the obstacles that influence the archive digitization process at the National Archives of the Republic of Indonesia. Researchers collect data by visiting the research location directly. Research data was obtained through literature studies such as journals, books, direct observation by going into the field, and interviews with informants related to the topic studied. The research method used is descriptive analysis which aims to explain or describe a situation or phenomenon that occurs. This method allows researchers to export aspects more widely. The researcher selected 4 (four) informants who met the criteria based on the research objectives so that the researcher obtained clear and accurate information in the form of statements, information or data that could help in understanding the problem. It is hoped that the results of this research will add insight into the implementation of archive digitization.